(untitled) - Habakkuk, H. J. (Cambridge, 1967)
This essay is a foray into the debatable borderland between history, technology and economics. On the history of technical processes there exist several works, pre-eminent among them the great five-volumed History of Technology. But few historians of technology have shown interest in the models of the economists; and the theorists have concentrated on analysis or on problems of contemporary technology. The present work is an attempt to re-examine some of the more familiar nineteenth-century developments in technology. It originated in lectures given at Columbia University in the autumn of 1958.
Keywords: Technology,Công nghệ; History,Lịch sử; United States,Hoa Kỳ